Adição de resíduo de louça sanitária como agregado em diferentes formulações de concreto - Almeida, Diego Henrique De (2017)
Among the inputs used in civil construction, concrete is one of the most used. Concrete can be made for structural purposes (bridges, buildings and other structures of reinforced or precast concrete) or for non-structural purposes (sidewalks, pavements, posts, dormant, blocks for shoes, among others). In concrete manufacture, cement (Portland cement is the most used), water and aggregates (classified into coarse and fine). With the use of several raw materials the generation of waste is inevitable, both in construction and in other sectors, such as the industries producing ceramic materials. Among the types of residues coming from such industries, there are those from the production of sanitary ware (called in this research as ceramic scrap). The aim of this research was to study the addition of ceramic scrap in substitution to the coarse aggregate in different concrete formulations. For this purpose, scrap ceramic was selected in an industrial plant in the southern state of Minas Gerais, and different mixes of concrete were prepared to determine physical properties (slump test, adhesiveness and porosity) and mechanical property (compressive strength). Five formulations, one reference (CR) and four with ceramic scrap were prepared in proportions of 25% (CSC-I), 50% (CSC-II), 75% (CSC-III) and 100% (CSC-IV) in substitution of the coarse aggregate. In the fresh state, two formulations did not show adhesiveness (CSC-III and CSC-IV) and two a small water runoff (CSC-I and CSC-II), However, without compromising the workability of the concrete, being classified, according to the consistency class for use in slender structural elements or with high density of reinforcements. Regarding the compressive strength, the average values ​​presented for all formulations were very good, including the formulation with 100% of ceramic scrap (fcm = 47.78 MPa). Concrete formulations with scrap ceramic are classified as C35 and C40, according to the values ​​of fck, being possible to be used in structures. An important aspect observed in the rupture modes of the specimens was the small adhesion between the ceramic scrap and the mortar due to the enamel in the contour of the residue. As for the porosity of the concretes, those with 25%, 75% and 100% of ceramic scrap in their composition presented lower values ​​than the reference concrete.